ACL injury mechanism in elite and recreational football players - Mayntzhusen, T.; Andersen, F. F.; Hölmich, P.; Kaldau, N. C. (BMJ Open Sport & Exercise Medicine, 2026)
Introduction An injury to the anterior cruciate ligament (ACL) is considered one of the most serious knee injuries in football, leading to the most time lost from competition. The study aimed to investigate the ACL injury mechanism in football across a cohort of elite and recreational players.